BIOFERMENTASI JERAMI PADI DENGAN PROBIOTIK MIKRO ORGANISME EFEKTIF MENJADI PAKAN TERNAK SAPI DI DESA KERTA KECAMATAN PAYANGAN GIANYAR - Siti, N.W; Witariadi, N.M.; Candraasih K., N.N.; Puja, N; Sukmawati, N.M.S.; Roni, N.G.K. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Devotion that aims to improve the knowledge and skills of farmers on rice straw biofermentasi with effective microorganisms into cattle feed, has been held in the Kerta village livestock groups Kerta Winangun, Payangan Gianyar on Sunday, August 21, 2016. The method used is a demonstration, counseling and mentoring of biofermentasi rice straw with effective microorganisms into cattle feed. Results of devotion are: (1) knowledge and skills of farmers about bioferemntasi rice straw into cattle feed has increased from 20% to 90%; (2) farmers 90% have been able to make rice straw silage using microbial effective; (3) farmers've tried 80% giving rice straw silage in cattle and (4) the crude protein content of rice straw increased from 4.33% to 7.32%. The conclusion of the public service are: (1) herd Kerta Winangun been able to make use of rice straw silage microbes effectively as cattle feed and (2) the crude protein content of rice straw silage increased.